Peran Kepuasan dalam Mengoptimalisasi Kinerja dari Aspek Kompensasi dan Motivasi Pegawai di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Teluk Bintuni - Nurheni Latif; Siti Fatonah; Anggoro Panji Nugroho (STIE AUB Surakarta, 2025)
This study examines the influence of compensation and motivation on employee performance at the Investment and Integrated One-Stop Service Agency of Teluk Bintuni Regency, considering job satisfaction as an intervening variable. Using a descriptive quantitative method and multiple linear regression analysis, this study involved 30 employees as samples. The results show a significant influence of compensation and motivation on employee job satisfaction at the Investment and Integrated One-Stop Service Agency of Teluk Bintuni Regency, with compensation contributing more significantly (79% of job satisfaction variation). Although compensation and motivation simultaneously have a significant influence on employee performance, the direct influence of compensation is not significant, while job satisfaction has a significantly larger positive influence. Motivation also has a positive and significant influence on performance, both directly and indirectly through increased job satisfaction. The low Adjusted R Square in the employee performance model (0.278) and R Square in the linearity test (0.002) indicate that other factors outside the model, such as work environment and leadership, play a significant role in explaining employee performance. Therefore, improving employee performance requires a comprehensive strategy that includes improving compensation and motivation to enhance job satisfaction, as well as paying attention to other contextual factors that influence performance. The recommendations include evaluating compensation policies, competency development programs, and a fair and transparent reward system. This study provides valuable insights for management to formulate effective strategies for improving performance and job satisfaction, as well as enhancing public service effectiveness.